BLADDER CANCER: DIFFERENTIATION OF TYPES, AGE, SEX DISTRIBUTION AND ASSOCIATED VARIANTS WITH GRADATION - Okbah, Amin Abdulkarem; Al-Ankoshy, Azhar Azher Mohammed; Al-Shamahy, Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2022)
Background: Urinary bladder cancer (UBC) is the ninth most common cancer in the world, and the third most common cancer among men in West Asian countries, including Arab countries. Despite the increasing prevalence of UBC in developing countries, many places, including Yemen, do not have representative studies showing the true impact of these tumors on the population. Aims: To describe the different types of bladder cancers, and their distributions with age, and sex and to correlated different types with gradation, invasion muscles; and schistosomiasis in the last ten years in a single Yemini institute. Materials and methods: An observational descriptive study was performed on UBC patients who were subsequently diagnosed selectively by histopathological study in the Department of Pathology at the National Center for Public Health Laboratories (NCPHL) Sana’a, Yemen, over a period of about 10 years from January 1, 2012 to October 31, 2021. The study variables were cancer histological type, sex, grades and age. Types, grading and histological diagnoses were formed in line with the World Health Organization classification of bladder cancer. Results: Most of the cases were in the age group 60-69 years (32%), followed by 70 years (22.3%), and 50-59 years (20%). The most common UBCs were urothelial neoplasms (UNs) (71.5%), followed by squamous neoplasms (SNs) (24.4%) while other types were less frequent. There was a cytologically high grade with a significance rate (64.2%) with UNs. There was a significance rate of: schistosomiasis (43.8%) with SNs as OR=19.5 (p < 0.001), and invasion of muscle fibers (66.4%) with SNs as OR=3.3, UNs (37.1%) as OR=11.2 (p < 0.001). Also there was a significance rate of GII grade (46.1%) with SNs as OR=64.1 (p<0.001) and GNs (33.3%) as OR=3.8 (p =0.02). Conclusion: The present study verification data congruence with those in the international literature and reports of neighboring countries, with some minor differences. This study documents a high incidence of urothelial neoplasms, with a male predominance and a peak incidence in the sixth decade of life. Imminent studies are needed to identify risk factors that increase cystitis in more detail and to study genetic susceptibility to inflammation and inflammatory markers before cancer is diagnosed. Peer Review History: Received: 12 October 2021; Revised: 9 November; Accepted: 13 December; Available online: 15 January 2022 Academic Editor: Dr. Nuray Arı , Ankara University, Turkiye, ari@ankara.edu.tr Reviewers: Dr. Bilge Ahsen KARA, Ankara Gazi Mustafa Kemal Hospital, Turkey, ahsndkyc@gmail.com Dr. Eyassu Mathewos, School of public health, college of health sciences and medicine, Wolaita Soddo university- P.O. Box 158, Wolaita Soddo, Ethiopia. Md. Monirul Islam, Department of Pharmacy, Faculty of Health Sciences, Northern University Bangladesh, Dhaka, Bangladesh. monirul.islam@nub.ac.bd Dr. Rawaa Souhil Al-Kayali, Aleppo University, Syria, rawah67@hotmail.com